1991
DOI: 10.1002/jso.2930480208
|View full text |Cite
|
Sign up to set email alerts
|

Metastases to the breast: Differential diagnosis from primary breast carcinoma

Abstract: Eight patients with breast metastases from primary tumors other than breast carcinoma were studied: 3 malignant melanomas, 2 rhabdomyosarcomas, 1 malignant mesothelioma, 1 appendiceal carcinoid, and 1 epidermoid cervical carcinoma. All had mammographic, histopathologic, and immunohistochemical examinations. The main problem was differential diagnosis from primary breast carcinoma. History of extramammary primary tumor was helpful but breast metastasis was the first clinical feature in 2 cases. Patients had not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
167
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(181 citation statements)
references
References 28 publications
7
167
0
1
Order By: Relevance
“…This finding has also been previously reported in the literature. 30 Similarly to the above, a contributing factor to these interpretations is the fact that the majority of these tumors presented as a solitary lesion in the breast and/or axilla.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This finding has also been previously reported in the literature. 30 Similarly to the above, a contributing factor to these interpretations is the fact that the majority of these tumors presented as a solitary lesion in the breast and/or axilla.…”
Section: Discussionmentioning
confidence: 96%
“…[25][26][27][28][29][30][31] In two different series of metastatic tumors to the breast, each reported four adolescent girls with metastatic rhabdomyosarcoma involving the breast. The alveolar subtype has been reported to occur much more commonly than embryonal, which is well known to be much more aggressive.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of secondary metastasis to the breast is uncommon and rarely reported. It is represented by nearly up to 2% of all breast swelling which account for nearly 400 cases that have been reported in the literature [2]. Malignant melanoma, leukaemia and lymphoma are the most common among all malignancies that have been described metastasizing to the breast [2].…”
Section: Discussionmentioning
confidence: 99%
“…The younger age of women suggested that the breast is a favorite site for metastasis because of a relatively rich blood supply (Vergier et al, 1991;Shiraishi et al, 2001). On the other hand, Vergier et al (1991) also hypothesized that estrogen may promote extramammary tumorigenesis. Gastric cancer seems to be more aggressive in younger people with hormonal factors implicated.…”
mentioning
confidence: 99%